CONCERING THE INTERRELATION OF E-LEARNING CONCEPTS IN HIGHER EDUCATION - B. E. Starichenko; I. N. Semenova; A. V. Slepukhin (Образование и наука)
The research objective is the classification and conventional interpretations of the concepts of «e-learning», «distance learning» and «blended learning»; its interconnection and correlation of the didactic system of modern education. The authors note that the deficiency of general data theories in pedagogical literature, - on the one hand, and active development of learning types essentially complicate framing and contents of modern education didactic system. Methods. The authors give the key feature of the generic difference betweenthe traditional and e-learning on the basis of the analysis and correlation made by various researchers’ viewpoints; the key feature - the information resources’ usage in educational process (i.e. devices for data processing, storage, transmission), and the information is presented in digital format. The authors single out that blended learning means implementation of traditional types and methods of specific educational tasks including the e-learning elements. Distance learning is proposed to be electronic itself; it’s supposed to be the final variation of e-learning.Scientific novelty and practical significance. The presented approach based on the digital resources’ level application permits to determine all-existing higher education learning types; to establish connection and show differences between them. The authors draw the conclusion that recommended approach can be usedfor further methodology development of modeling the specialists’ training variants in higher school. It is specially noted that this very training is considered as the collaboration of teachers and students focused on knowledge acquisition, work methods and communication features that correspond the future profession requirements. A mention should be made that it is necessary to use educational information material supplement and needed electronic devices or equipment.